Intelligence and good governance on socioeconomic development of global community - Ahmad Suhaimi, Siti Shazwani (2021)
A positive connection between intelligence (measured as IQ) and happiness at the country level has been described repeatedly. The present study treats IQ as an important source of human and social capital, and ultimately of happiness and life satisfaction. Furthermore, it was revealed that the national average intelligence (IQ) also is a strong indicator in determining national entrepreneurial potential. Considering that the public institutions are responsible to serve the needs of the majority, this study specifically examined the moderating effect of governance quality on the relationship between national average IQ upon happiness and entrepreneurial activity measured as new business entry density at a cross-country level. This is a quantitative study where the data required were based on secondary data, from World Bank database,World Health Organization (WHO) and World Happiness Report (WHR). The results of robust regression analysis revealed that national IQ was highly significant in raising the level of happiness. Furthermore, the interaction between IQ and governance quality contributed a positive and significant effect on happiness. The conclusion is that governance quality enhances the positive impact of intelligence on happiness. Good governance appears to create the conditions under which higher national IQ can be used towards achieving a higher level of well-being. Employing robust regression analysis, IQ was found to be non-significant on entrepreneurial activity, while the effect of governance was found to be both positive and significant. However, there was strong evidence of the negative interaction between IQ and governance, which suggests that good governance raises entrepreneurial activity more in low-IQ than in high-IQ countries. Additional regressions were also carried out employing the ease of doing business (EDB) index as a measure of entrepreneurship. The results demonstrated that IQ, and not governance was highly significant on the EDB. Moreover, the interaction between IQ and governance was non-significant, which implies that the governance quality did not regulate the effect of IQ on the EDB. This study concluded that national average IQ is effective at providing nations with an excellent regulatory environment for entrepreneurship. However, it requires good governance, and not IQ, in order to build people’s confidence before they start new entrepreneurial ventures given it involves risks and uncertainty.